Effects of Septoglomus constrictum and Bacillus cereus on the competitive growth of Ageratina adenophora - Du, Ewei; Chen, Yaping; Li, Yang; Li, Yahong; Sun, Zhongxiang; Hao, Ruoshi; Gui, Furong (Frontiers in Microbiology, 2023)
Beneficial microorganisms play a pivotal role in the invasion process of exotic plants, including arbuscular mycorrhizal fungi (AMF) and Bacillus. However, limited research exists on the synergistic influence of AMF and Bacillus on the competition between both invasive and native plants. Pot cultures of Ageratina adenophora monoculture, Rabdosia amethystoides monoculture, and A. adenophora and R. amethystoides mixture were used to investigate the effects of dominant AMF (Septoglomus constrictum, SC) and Bacillus cereus (BC), and the co-inoculation of BC and SC on the competitive growth of A. adenophora. The results showed that inoculation with BC, SC, and BC+SC significantly increased the biomass of A. adenophora by 14.77%, 112.07%, and 197.74%, respectively, in the competitive growth between A. adenophora and R. amethystodes. Additionally, inoculation with BC increased the biomass of R. amethystoides by 185.07%, while inoculation with SC or BC+SC decreased R. amethystoides biomass by 37.31% and 59.70% compared to the uninoculated treatment. Inoculation with BC significantly increased the nutrient contents in the rhizosphere soil of both plants and promoted their growth. Inoculation with SC or SC+BC notably increased the nitrogen and phosphorus contents of A. adenophora, therefore enhancing its competitiveness. Compared with single inoculation, dual inoculation with SC and BC increased AMF colonization rate and Bacillus density, resulting in significantly higher A. adenophora biomass. This study reveals the distinct role of S. constrictum and B. cereus during the invasion of A. adenophora. S. constrictum provides a competitive advantage to invaders by accumulating higher N and P contents, while B. cereus activates available nutrients in the rhizosphere soil for plant absorption. Altogether, the synergistic inoculation of AMF and B. cereus strengthens the competitiveness of the invasive plant A. adenophora.